Impact of percutaneous nephrolithotomy operation on non-operated kidney: a single center based study - Samaddar, Debasis; Sarkar, Debansu; Pal, Dilip Kumar; Gupta, Sandeep (International Journal of Research in Medical Sciences, 2019)
Background: Effects of percutaneous nephrolithotomy (PCNL) operation on ipsilateral renal function are widely known but functional changes in opposite kidney are limited. Authors have conducted this study to evaluate the impact of PCNL operation on the contralateral side during early post-operative period. Methods: From 1st November 2016 to 30th September 2018, those patients presented with unilateral renal stone disease were enrolled. After exclusion they were subjected to PCNL operation under general anaesthesia. Along with preoperative period, 99 m Tc DTPA renal scan is repeated at 3rd and 14th post-operative period. Results: Out of 121 patients enrolled we included 96 patients after exclusion. They are divided into 3 age groups, 19-32, 33-47 and 48-60 years. The mean GFR at pre-operative, post-operative day-3 and 14 of normal kidney in these 3 age groups are 47.32, 47.63 and 42.32 ml/min, 44.29, 45.78 and 40.63 ml/min and 47.10, 48.47 and 41.01 ml/min respectively. At post op day-3 there are reduction of mean GFR in all age groups but statistically not significant (p >0.05). At post-operative day-14 GFR improved towards the pre-op value but the change is also not significant (p >0.05). Conclusions: There are reduction of GFR of contralateral normal kidney following PCNL operation in early post-operative period. So, along with operated kidney normal kidney also showed decrease GFR. It is better to avoid further trauma in post PCNL patient like avoidance of using nephrotoxic medication, contrast agents, ESWL, etc. This study can guide us to avoid further trauma of any kidney.